Laughing With You or Laughing at You: The Influence of Playfulness and Humor on Employees’ Meeting Satisfaction and Effectiveness - ` Pham, Tri H.; Bartels, Lynn K. (Journal of Organizational Psychology, 2021)
Employees spend a significant amount of work time in meetings that they find dissatisfying and ineffective. We examined the influence of play and humor on perceptions of meeting effectiveness and satisfaction. Specifically, a Meeting Playfulness scale was developed to measure the relationships between playfulness (as a state) and meeting effectiveness and satisfaction. Findings indicated that positive humor, negative ingroup humor, negative out-group humor, and play contributed to perceptions of meeting effectiveness. Meanwhile, positive humor, negative out-group humor, and play contributed to meeting satisfaction. The results from this study suggest that play and certain aspects of humor can contribute positively to meeting outcomes. Future research directions include examining play and humor in virtual meetings and the influence of cultures and norms on participants’ willingness to engage in play and humor in group settings.